Մարդու և առաջնորդի կերպարը Ն. Շնորհալու «Թուղթ ընդհանրականում» («Թուղթ ընդհանրականի» 850-ամյակի առթիվ) - Յուրի Սուվարյան; Արծվիկ Սուվարյան (ՀՀ ԳԱԱ հրատ.)
Прозаическое произведение великого армянского мыслителя, поэта, сочинителя духовных песен, теолога, политического и церковного деятеля Нерсеса Шнорали «Соборное послание» было создано в 1166 году и многократно переиздано в XVIII–XX веках в Санкт-Петербурге, Венеции, Константинополе, Эчмиадзине, Иерусалиме, Антилиасе, Ереване. The prosaic work of the great Armenian philosopher, poet and writer of spiritual songs, theologian, political figure and churchman Nerses Shnorhali, "A Monastic Message" was created in 1166 and was reprinted many times in the 18th–20th centuries in St. Petersburg, Venice, Constantinople, Etchmiatsin, Jerusalem, Antelias, Yerevan.
Keywords: Literature; Language and Literature